Matices del feminismo: Estrategias y colores del discurso feminista en Instagram - Chávez, Gianella (2021)
The objective of this investigation is centered on the identification, analisis and comparison of the feminist discourse that has been spread on the social network: Instagram. The methodology used is virtual ethnography, through which monitoring and following took place for the three influencer accounts @empoderadamente_pe, @rominacastrosexologia y @corazónconleche. The interactions maintained with the users through comments and “likes” were gathered and the content of the posts with most engagement, its tags and main topics were analyzed, for a posterior categorization within the waves of feminism, according to the strategy selected and utilized in the elaboration of the discourse. In the results, the tendency of the use of the color pink and similar tones was recognised, as a way of re-signifying to connect with women in a dispersed environment. The topics addressed vary between the three users, according to the branch or type of feminism desired to develop. The most used formats are illustrations and the approach given by the posts tends to inform or share a reflection that incites a behavioural change. To conclude, it was discovered that the feminist discourse within Instagram tends to form on the base of the same conceptual center, which takes women as protagonists and intends to empower her through content spread as illustrations, which resignify what is understood as femenine through the color pallet. It was also observed that influencers allocate their own discourse, that is portrayed using diverse strategies. That is the reason why it is not possible to catalog all of the accounts inside the fourth feminist wave.